MENINGKATKAN VOLUME PENJUALAN ONLINE MELALUI STRATEGI PACKAGING DI KELURAHAN KEMBANGAN UTARA - Hamdan Hamdan; Amzad Samudro; Deden Kurniawan; Mochamad Rizki Sadikin (Universitas Mercu Buana, 2021)
Improving the creative economy of environmental quality and human resources in North Kembangan through a packaging strategy in increasing online sales volume is a form of Corporate Social Responsibility (CSR) at Mercu Buana University in realizing the Tri Dharma of Higher Education. The service through the development of the creative economy and environmental quality carried out by the PKM Team of the Faculty of Economics and Business, Mercu Buana University together with the community partners of North Kembangan, went according to expectations. The contribution of activities increases insight and knowledge of how packaging strategies can increase the volume of sales during the Covid-19 pandemic. Especially creating competitive advantage and realizing the sustainability of the cooperation partners' business in the future. The packaging strategy is an important factor as the main consideration for consumers to have a positive attitude and behavior towards the products offered. The importance of implementing a packaging strategy by collaborative partners to support this program in a sustainable manner, of course in encouraging and improving the creative economy of North Kembangan.